Molecular and Clinical Characterization of a Recurrent Cryptic Unbalanced t(4q;18q) Resulting in an 18q Deletion and 4q Duplication. - Horbinski, Craig (2008)
Recurrent constitutional non-Robertsonian translocations are very rare. We present the third instance of cryptic, unbalanced translocation between 4q and 18q. This individual had an apparently normal karyotype; however, after subtelomere fluorescence in situ hybridization (FISH), he was found to have a cryptic unbalanced translocation between 4q and 18q [ish der(18)t(4;18)(q35;q23)(4qtel+,18qtel−)]. Oligonucleotide array comparative genomic hybridization (aCGH) refined the breakpoints in this child and in the previously reported child and indicated that the breakpoints were within 20 Kb of each other, suggesting that this translocation is, indeed, recurrent. A comparison of the clinical presentation of these individuals identified features that are characteristic of both 18q− and 4q+ as well as features that are not associated with either condition, such as a prominent metopic ridge, bitemporal narrowing, prominent, and thick eyebrows. Individuals with features suggestive of this 4q;18q translocation but a normal karyotype warrant aCGH or subtelomere studies.